Polymeric coatings for surface decontamination and ecofriendly volume reduction of radioactive waste after use. (April 2018) - Yang, Hee-Man; Park, Chan Woo; Lee, Kune-Woo
Abstract: A magnet-sensitive and strippable polymeric coating that consists of a magnetic adsorbent with 137 Cs adsorption properties using a polyacrylamide (PAAm)/alginate(Alg)-based hydrogel with highly elastic properties was developed for surface decontamination. The aqueous polymeric solution of PAAm and Alg containing adsorbent could be easily applied to 137 Cs-contaminated surfaces via the brush method. The simple addition of calcium ions on the surface induced the formation of an adsorbent/PAAm-Alg hydrogel film that could easily peel away from decontaminated surfaces due to its high elasticity. This polymeric coating displayed a good removal efficiency of 96.53% and a decontamination factor (DF) of 28.85 for 137 Cs-contaminated surfaces due to the presence of the adsorbent, which had a large distribution coefficient for Cs (3.34 × 10 4  mL/g), and the large amount of Cs chelating groups in the Alg and PAAm, such as carboxyl and amine groups. The generated volume of the radioactive wastes after surface decontamination was simply reduced due to the magnetic separation of the adsorbent from the used polymeric coating. Furthermore, this new ecofriendly volume reduction method for radioactive waste demonstrated the reusability of PAAm and Alg for further surface decontamination because almost all of the 137 Cs (99.838%) captured in the used polymeric coating was removed by magnetic separation of the adsorbent. Therefore, the adsorbent/PAAm-Alg-based polymeric coating system has excellent potential as a new cost-effective surface decontaminant. Graphical abstract: Highlights: The polymeric coating composed of magnetic Cs adsorbent, polyacrylamide, and alginate were developed. The strippable coating film formed by simple addition of Ca ions effectively removed 137 Cs from the contaminated surface. The volume of radioactive wastes was reduced through the magnetic separation of the adsorbent from the used film. Our polymeric coating has good reusability and potential for the wide-area surface decontamination after nuclear accident.